2007
DOI: 10.1897/07-137
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity and Genotoxicity Assessment of Cytostatic Pharmaceuticals

Abstract: The fate and effects of cytostatic (anticancer or antineoplastic) pharmaceuticals in the environment are largely unknown, but they can contaminate wastewater treatment effluents and consequently aquatic ecosystems. In this paper, we have focused on five cytostatic compounds used in high amounts (cyclophosphamide, cisplatin, 5‐fluorouracil, doxorubicin, and etoposide), and we have investigated their ecotoxicity in bacterial Pseudomonas putida growth‐inhibition test, algal Pseudokirchneriella subcapitata growth‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…3C). The cytostatic effect of 5‐fluorouracil in mammalian cells is well described [13], and yeast cells are currently being used to study its mechanisms of action in the cell cycle and metabolism [14,15]. However, the exponential decay curve reported here for 5‐fluorouracil in yeast is new and has not been shown for other antitumoral drugs.…”
Section: Resultsmentioning
confidence: 97%
“…3C). The cytostatic effect of 5‐fluorouracil in mammalian cells is well described [13], and yeast cells are currently being used to study its mechanisms of action in the cell cycle and metabolism [14,15]. However, the exponential decay curve reported here for 5‐fluorouracil in yeast is new and has not been shown for other antitumoral drugs.…”
Section: Resultsmentioning
confidence: 97%
“…The occurrences of these drugs in the aquatic environment could be 78 especially critical since they are intrinsically hazardous. Several ecotoxicological studies 79 have shown that in some cases such as for the cancer drug 5-Fluorouracil, the lowest 80 observed-effect concentration values (in algal and bacterial assays) were close to the 81 concentration found in sewage effluents (Zounkova et al, 2007) . More recently, studies 82 have revealed that mixtures of anticancer drugs in real samples possess an important 83 toxicological effect comparing with the individual drug (Mater et al, 2014).…”
Section: Introduction 69mentioning
confidence: 87%
“…Environmental concerns relating to the use of topoisomerase inhibitors have increased. Topoisomerase inhibitors exert detrimental effects to diverse wild life, including bacteria, aquatic organisms (planktons and primary consumers), and plants . However, in these reports, the toxicological evaluation is limited to growth inhibition; the detailed cellular and molecular mechanisms underlying the toxicity of topoisomerase inhibitors have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%